Two-Scale Estimates for Special Finite Discrete Operators - Vasilyev, Alexander V.; Vasilyev, Vladimir B. (Mathematical Modelling and Analysis, 2017)
We consider a certain finite discrete approximation for multidimensional Calderon–Zygmund integral operator and give a comparison between solutions of corresponding equations in some spaces of discrete functions.